Vena cava filter options: what's on the horizon?. (2nd April 2016) - Lessne, Mark L.; Rinaldi, Michael J.; Sing, Ronald F.
ABSTRACT: Inferior vena cava (IVC) filters are the mainstay for pulmonary embolic prophylaxis in patients with high venous thromboembolic (VTE) risk—in particular, patients with acute VTE (deep venous thrombosis and/or pulmonary embolism) who have contraindication to therapeutic anticoagulation. Technology continues to evolve regarding IVC filters, with the most exciting changes over the past several decades including techniques of percutaneous insertion from laparotomy and retrieval of these devices. This paper will review current IVC filter designs and concepts and will discuss developments on the horizon.